Synthesis of a new adsorbent based on polyacrylonitrile fibers coated by potassium–copper ferrocyanide for the selective removal of cesium from contaminated waters - Bondar, Yu. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
A new composite adsorbent is synthesized by the in situ deposition of a potassium–copper ferrocyanide layer on the surface of modified polyacrylonitrile fibers. The synthesized adsorbent has demonstrated a rapid adsorption and the selectivity in the cesium ion removal from highly mineralized solutions.